How to prioritise in quality improvement? Targeted implementation as a key for quality improvement in Kenyan health facilities. Issue 4 (19th November 2020) - Nitschke, Christine; Nafula, Maureen; Brodowski, Marc; Marx, Irmgard; Kandie, Charles; Omogi, Irene; Paul-Fariborz, Friederike; Szecsenyi, Joachim; Brugnara, Lucia; Marx, Michael
Abstract : Background: Data from national surveys of low- and middle income countries indicates that there is still a need to improve the quality of healthcare in resource-poor settings. This study aims to understand the benefit of an integral, facility-driven, indicator-based approach used as a decision-making tool to define effective quality improvement interventions in Kenya. Objective: The aim of the study is to understand whether the integral approach developed leads to effective interventions. Methods: Categorical data is collected from ten health facilities covered by the Integrated Quality Management System (IQMS) project in Kenya. First the information on concrete improvement interventions implemented within the facilities is collected and merged into five different intervention topics. Second, groups of facilities with similar quality improvement interventions are selected to compare between the first and second quality assessment rounds. Those IQMS indicators matching the content of the intervention topic are extracted from the software VISOTOOL. In a third step, the data is summarised using means and SD. A one sample T-test is applied on the mean changes and SD. Frequency counts and percentages were used for the presentation of categorical data. Results: All improvement interventions resulted in positive and higher change values (T2-T1). Four of five intervention topics, show statistically significant improvements including neonatal mortality (42%; p<0.0001), waiting time (39%; p=0.0490), infection prevention control (28%; p=0.0007) and with shortages of staffing and transport in remote areas (32%; p=0.0194). Conclusions: In all facilities the interventions selected have a positive impact, some of which markedly improved. It demonstrates that this integral quality improvement approach in Kenya can serve as an effective decision-making tool for identification and prioritisation of interventions. Those targeted interventions, being performed under institutionalisation in form of coaching and tutoring, effectively contribute to improving the quality of care in resource poor settings.